The Impact Effect of Corporate Governance and Corporate Social Responsibility on Company Performance After the Financial Tsunami - Chung, Li-Hui; Wei, Ching-Chun (Asian Journal of Economic Modelling, 2017)
This article discusses corporate governance after the recent financial crisis and its relationship with corporate performance by adding in the CSR variable. The empirical study investigates the top 50 Taiwanese electronics companies as denoted by Commonwealth Magazine, which are listed on the Taiwan Composite Stock Exchange or in the Over the Counter (OTC) market over the period 2009-2014. Company data come from the Taiwan Economic Journal (TEJ) Database, while CSR winners are from Wealth Magazine CSR Awards. The empirical results show that corporate governance and corporate performance do have a significant relationship. In ROA, the cross effect of shareholding ratio and CSR is supported empirically, while in ROE, the cross effect of the largest shareholder ratio and CSR is supported empirically. Through the adjustment factor of CSR, managers are able to understand its deeper meaning and its correlation to corporate governance. While CSR activities cost companies a lot of time and money, fulfilling such social responsibility benefits are reflected in a company’s financial performance and can be used as a useful reference for decision-making.